Bilingualism and Bilingual Education in Iceland: A Study of the Importance of Mother Tongue Support for Bilingual Children in Iceland - Shukurova, Maria, 1984- (2009)
The following paper discusses the phenomenon of bilingualism and bilingual education in Iceland. It reports on the results of a survey among parents of bilingual children investigating the importance of mother tongue teaching. The first part of the paper focuses on the difficulty in defining the concepts of bilingualism and bilingual education in particular. An overview of individual and societal bilingualism from historical and modern perspective as well as various examples of bilingual education are described. References to Jim Cummins and his research in bilingual education are provided to support the notion that mother tongue teaching on a regular basis is important to the general language development of bilingual children. Special attention is given to the overview of bilingualism and bilingual education in Iceland. Examples of mother tongue support in Iceland, including the volunteer organization, Móðurmál (the Mother Tongue Association), are presented. The second part of the paper includes results and discussion of a survey that was designed to collect information about participants’ perceptions of their and their children’s L1 and L2 proficiency, linguistic and social identity and attitude towards mother tongue teaching among bilingual children attending language classes at the Mother Tongue Association. Respondents were parents of bilingual children from four different language groups that were asked to complete a questionnaire. Conclusions were drawn from the received responses. The conclusions show that responses differ from one language group to another, which is influenced by social and linguistic differences between represented cultures. However, all the respondents stated that mother tongue support is an important part of the educational process. Thus, most subjects were positive about the implementation of mother tongue support in schools.